Asia and Climate Change: How It Will Play Out From the Bosporus to Djakarta (Asian Journal of Social Science Studies, 2018)
Now that the measure of CO2 emissions has broken through 410 on the standard Keeling curve (Earth CO2 website), one may start drawing a scenario for climate change repercussions, here for the Asian continent. It pollutes most of all continents in terms of both greenhouse gases and many other pollutants. The threats to mankind comes in the form of sea level rise, fresh water shortage, less of potable water, shrinking of lakes and rivers, deoxygenation of oceans, less fish food and agriculture produce, energy shortages, omnipresent air conditioning, urban smog, water and sea pollution due to sewage and failures with landfills. Asia, hosting more than half of mankind, will suffer massively from global warming with millions of ecological refugees. The UN’s program, the COP21 by the UNFCCC, cannot stop Asia from reaching Hawking irreversibility, because it entails too weak global governance that is cheatable. The promise of complete decarbonisation is an illusion.